2016
DOI: 10.1136/jech-2015-206543
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to reduce childhood antibiotic prescribing for upper respiratory infections: systematic review and meta-analysis

Abstract: Educational interventions are effective in reducing antibiotic prescribing for childhood URIs. Interventions targeting clinicians and parents are more effective than those for either group alone. The most effective interventions address patient-clinician communication. Studies in low-income to middle-income countries are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 36 publications
1
44
0
8
Order By: Relevance
“…A recent trial in the USA showed that use of guidelines, recording justifications for antibiotic use and peer review was effective in reducing inappropriate antibiotic use . We further added interventions at the patient side in a prospective trial as targeting both doctors and patients has shown a larger effect than targeting only one of them, .…”
Section: Discussionmentioning
confidence: 99%
“…A recent trial in the USA showed that use of guidelines, recording justifications for antibiotic use and peer review was effective in reducing inappropriate antibiotic use . We further added interventions at the patient side in a prospective trial as targeting both doctors and patients has shown a larger effect than targeting only one of them, .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings regarding limited public understanding about the potential harms of antibiotic overuse are reflected in other studies, which suggest that patients may lack awareness and/or may not view this issue as personally relevant . Furthermore, two systematic reviews of interventions aimed at reducing antibiotic prescriptions for children with respiratory tract infections found that the most effective interventions simultaneously target parents and clinicians . Deliberation participants echoed that interventions should not target patients or physicians alone but also noted that government stakeholders have roles in controlling this problem too.…”
Section: Discussionmentioning
confidence: 55%
“…The stewardship programme includes: (1) building up the antibiotic stewardship leadership, (2) developing operational guidelines, (3) conducting appropriate antibiotic prescribing training with family physicians and village doctors, (4) employing EMR and smart phone apps as reminders and prescription review tools and (5) educating patients during and after consultations. Systematic reviews have shown that broader interventions targeting both health providers and patients achieve the largest effect [6,24]. In this trial, we will target uncomplicated ARIs for all ages which will be more useful to family physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions addressing inappropriate antibiotic prescribing in primary care that only target patients often show no impact, while effective interventions have employed multi-component strategies that improve the knowledge, attitudes and behaviours of both healthcare providers and patients [20][21][22]. However, most intervention trials have been done in high-income countries [23,24]. We previously developed an intervention to reduce inappropriate antibiotic prescribing for childhood (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) years old) upper respiratory tract infections (URTIs) in rural, public, primary care facilities known as township hospitals.…”
Section: (Continued From Previous Page)mentioning
confidence: 99%